Are 4D motion sensors valid and reliable for studying baseball pitching? - Loushin, S. R.; Verhoeven, M.; Christoffer, D. J.; Camp, C. L.; Kaufman, K. R. (The American Journal of Sports Medicine, 2023)
Background: Baseball pitching injuries are on the rise. Inertial measurement units (IMUs) provide immediate feedback to players and coaches, allowing for collection outside of the traditional laboratory setting with real-world application. The 4D Motion system provides kinematics throughout the pitching motion and may be beneficial for individualized programs in the throwing athlete. A systematic analysis of these sensors has not been completed.